Interface Theology. - Matheson, Peter (ATF Press, 2016)
InterfaceTheology is a biannual refereed journal of theology published in print, epub and open access by ATF Press in Australia. The journal is a scholarly ecumenical and interdisciplinary publication, aiming to serve the church and its mission, promoting a broad based interpretation of Christian theology within a trinitarian context, encouraging dialogue between Christianity and other faiths, and exploring the interface between faith and culture. It is published in English for an international audience.